Sosialisasi Dasar-Dasar Matlab Untuk Pembelajaran di Sekolah SMA Nurul Islam Indonesia Baru Jalan Megawati No. 20B Medan - Ahmad Yanie; Lisa Adriana Srg; Yussa Ananda; Indra Roza (Jurnal TUNAS, 2023)
As time progresses, it brings about changes that can transform everything. The technology that once used typewriters has now shifted to a device called a computer. With the presence of computers, its benefits are not overlooked by various parties. The benefits provided by computers offer convenience to those who need it. For example, an IT professional cannot be separated from the existence of computer functions in searching for various information. Likewise, workers in the education field utilize computers to support educational facilities. Along with the development of computers, the field of education also develops. There are many problems in education that can be solved manually. Many application programs or software can be used to solve problems, ranging from simple to complex, especially problems in Mathematics, such as the GeoGebra application. Matlab or Matrix Laboratory is software used for programming, analysis, as well as technical and mathematical computations based on matrices. Matlab was first released in 1970 by Cleve Moler. Initially, Matlab was used to solve problems related to linear algebraic equations. And to this day, the Matlab system continues to evolve in terms of its functions and computational performance.